Reflections on Decolonization: an Alternative to the Traditional Classroom - Revistas UPTC, Mariana Ibáñez Galindo; Sandoval, Gabriel Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The concept of colonization in education has multiple characterizations and is related to many teaching fields and theoreticians. It is commonly related to how teachers are colonizers of students’ minds with knowledge and how, sometimes, teachers are not aware of this responsibility. This article presents some reflections about decolonization processes underlying structured education and discusses the need to create teacher awareness and understanding of decolonizing practices and, in time, to spread it to other members of the academic community. The article presents a reflection process in five stages, based on different authors and the reflection from the discussion between this article’s authors.